DEVELOPMENT PROSPECTS OF THE RUSSIAN MARKET OF TECHNICAL SERVICING AND REPAIR IN THE СONTEXT OF A PANDEMIC - O. A. Tettsoeva (Вестник университета, 2021)
COVID-19 pandemic has made adjustments to the development of the country’s economy in terms of changing its structure in the industry context. The business community will invest in industries that will maximize profits with low payback periods. Currently, at a time of decreasing automotive production caused by the suspension of the plants in the period of lockdown, the reduction in purchasing power of communities connected with the risk of unemployment occurrence in consequence of business failures, the decline in wages and lower vacancy rates, is foreseen reduced demand for new cars against the background of significant increase in sales volumes in the used cars market segment and, therefore, sharp increase in demand for car services performing technical servicing and repair. In a competitive environment, it is the client of the car service who will determine the direction of business development, which will be carried out on the basis of digital technologies.